International Financial Statistics, February 2016. (International Financial Statistics; International Financial Statistics, 2016)
This February 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Borrowings are regarded as a temporary source of funds. In order to supplement its quota resources, the IMF has the authority to borrow the currency of any member from any source with the consent of the issuer. Data on international liquidity are presented in the country tables and in world tables on reserves. The international liquidity section in the country tables comprises lines for total reserves minus gold, gold holdings, other foreign assets and foreign liabilities of the monetary authorities, and foreign accounts of other financial institutions. IFS publish, for most countries of the world, current data on exchange rates, international liquidity, international banking, money and banking, interest rates, prices, production, international transactions, government finance, and national accounts.